How was it possible? : a Holocaust reader - Hayes, Peter, 1946 September 7- (University of Nebraska Press, 2015)
As the Holocaust passes out of living memory, future generations will no longer come face-to-face with Holocaust survivors. But the lessons of that terrible period in history are too important to let slip past. How Was It Possible?, edited and introduced by Peter Hayes, provides teachers and students with a comprehensive resource about the Nazi persecution of Jews. Deliberately resisting the reflexive urge to dismiss the topic as too horrible to be understood intellectually or emotionally, the anthology sets out to provide answers to questions that may otherwise defy comprehension.